2013
DOI: 10.1002/esp.3465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the response of various land covers to an exceptional rainfall event in the central Spanish Pyrenees, October 2012

Abstract: The hydrological and geomorphological effects of an exceptional 14 rainstorm event that occurred in the central Spanish Pyrenees during 19-21 October 15 2012 were studied in five experimental catchments under various land covers: (i) 16 subhumid badlands; (ii) dense forest; (iii) an abandoned farmland area recolonized by 17 shrubs and forest patches; and (iv) subalpine grasslands. Hydrographs and sedigraphs 18 demonstrated that vegetation cover is a major factor affecting the control of floods even 19 during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 63 publications
(82 reference statements)
1
28
0
1
Order By: Relevance
“…However as Lana-Renault et al (2014) showed, catchments that have been subjected to farmland abandonment tend to have hydrological behaviors that are similar to forested catchments, although the hydrological activation of eroded areas, resulting from past agricultural uses, explains a significant contribution of overland flow, and subsequent intense hydrological and sediment responses. Comparing the experimental catchments with the lacustrine watersheds, we found that the Izas catchment -deforested during Medieval times to provide summer grasslands -the Arnás catchment -entirely cultivated until the 1950s -and the San Salvador catchment -covered by an undisturbed vegetal cover -all have similar range of Sy in the catchments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However as Lana-Renault et al (2014) showed, catchments that have been subjected to farmland abandonment tend to have hydrological behaviors that are similar to forested catchments, although the hydrological activation of eroded areas, resulting from past agricultural uses, explains a significant contribution of overland flow, and subsequent intense hydrological and sediment responses. Comparing the experimental catchments with the lacustrine watersheds, we found that the Izas catchment -deforested during Medieval times to provide summer grasslands -the Arnás catchment -entirely cultivated until the 1950s -and the San Salvador catchment -covered by an undisturbed vegetal cover -all have similar range of Sy in the catchments.…”
Section: Discussionmentioning
confidence: 95%
“…The experimental catchment data have indicated that intense but infrequent flood events mainly control the sediment yield (Lana-Renault et al, 2014). For that reason, there is a large uncertainty in the estimation of long-term sediment production from a given catchment, and this is of critical importance for the management of the landscape-associated resources (water reservoirs, land use changes, abandon of cultivated lands, re-vegetation practices, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el caso de la urbanización, localizada en Castiello de Jaca, se había desviado un canal del cauce del río Aragón hacia la orilla opuesta y así dar una sensación de seguridad; sin embargo, durante la avenida el río sobreexcavó en la base de una terraza fluvial, que se desplomó sobre el cauce y obligó a éste a retomar el cauce primitivo, a cuyo costado se había construido la urbanización. De esta crecida pudo disponerse además de información detallada en cuatro cuencas experimentales del Instituto Pirenaico de Ecología, pudiéndose comprobar la notable importancia de la cubierta vegetal en la respuesta hidrológica (Lana-Renault et al, 2014a). Así, la cuenca de San Salvador, con un bosque denso no perturbado, esperó hasta el tercer pico de intensidad de lluvia para empezar a reaccionar, y su principal pico de avenida fue re-lativamente moderado en comparación con la cuenca de Araguás, caracterizada por la presencia de cárcavas sobre margas poco permeables.…”
Section: La Ocurrencia De Eventos Extremos Y Su Efecto Erosivounclassified
“…These findings have enhanced knowledge of the runoff generation processes operating in these catchments under different rainfall and moisture conditions , 2014cSerrano-Muela et al, 2008;Nadal-Romero et al, 2016). These results have also enabled comparisons of their hydrological Nadal-Romero et al, 2016) and sedimentological responses, even under extreme rainfall conditions (Lana-Renault et al, 2014b). The considerable data on meteorological, hydrological and sediment transport variables have been used to test and apply models to simulate soil erosion (Alatorre et al, 2012) and water and sediment yield under different land use scenarios, and to better understand the effect of revegetation on the main hydrological processes (Lana-Renault et al, in review).…”
Section: The Catchmentsmentioning
confidence: 74%